Strategies in Communicating and Enforcing COVID-19 Measures: A Rhetorical Analysis - Ndiritu, Nelson; Maina, Joseph (Universitas Pattimura, 2024)
This article investigates the rhetorical strategies used by national leaders in communicating and enforcing COVID-19 measures during the global health crisis. The study aims to analyze how persuasive language was employed to influence public behavior and ensure compliance with health protocols. Using a qualitative rhetorical analysis approach, the speeches of four prominent leaders—Donald Trump, Vladimir Putin, Boris Johnson, and Uhuru Kenyatta—were examined to identify the use of classical rhetorical appeals (ethos, pathos, and logos) and linguistic devices such as metaphors, enumeration, and authoritative tone. The findings reveal that each leader strategically adapted rhetorical techniques to their sociopolitical contexts, balancing emotional appeal, credibility, and logical reasoning to motivate collective action. The study highlights how language not only conveys information but also functions as a tool of power and influence, particularly in moments of crisis. The novelty of this research lies in its comparative cross-national approach and its focus on the intersection of rhetoric, leadership, and public health communication. This article contributes to the advancement of social sciences and humanities by offering a framework for understanding political discourse as a persuasive and performative act, and recommends incorporating rhetorical literacy in public communication strategies to enhance crisis response effectiveness in the future.